Gaudy Havoc: Iris Tree's performative decadent modernism. Issue 2 (4th May 2022) - Parker, Sarah
ABSTRACT: This article is the first detailed critical discussion of the modernist poet Iris Tree. Despite being a prolific poet and a regular contributor to the modernist magazine Wheels, Tree is today primarily remembered as a muse for others rather than a poet in her own right. I suggest that Tree's neglect is partly due to her playful incorporation of decadent modes in her work, rather than the rejection of the fin de siècle more usually associated with modernist writing. As my analysis of her poems shows, Tree uses decadent aesthetics to address the absurdity of war and to contemplate the boundaries of identity in her work. In this sense, a consideration of Tree's poetry has much to offer thriving areas of enquiry in modernist studies, including queer, camp, ornamental and decadent modernisms, as her exuberant and expansive incorporation of decadent tropes, personae and forms results in a multi-faceted, extravagantly performative poetics.